Sejarah Timbul dan Pokok-Pokok Ajaran Syi'ah Imamiyyah - N, Nurhasmi; Santalia, Indo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the history, development, and schools of the Shi'ah madhhab. Shi'ah literally means follower or supporter, while this term refers to the followers of Ali ibn Abi Talib, who believed Ali to be the chosen caliph of the Prophet Muhammad and the most important companion. After the events of the Battle of Jamal and Shiffin, the Shi'ah split into four groups. First, moderate Shiites who follow Ali without condemning the companions and still glorify them. Second, Tafdhiliyah, who believed that Ali was superior to other companions, represented the Shi'ah today. Thirdly, Saba'iyah, who considered all the Companions of the Prophet infidels and grave sinners, was led by Abdullah ibn Saba’. Fourth, Ghulat, a group of extreme heretics, believe that God has entered into the Prophet Jesus.